Relatório de estágio curricular supervisionado em medicina veterinária: na área de bovinocultura de corte - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This report describes the activities developed during the Supervised Curricular Internship in Veterinary Medicine, conducted by Arthur Bastos Bianchi at the Santa Helena Ranch of the GAP Genetics Group, located in Uruguaiana-RS. The internship, with a total duration of 450 hours, took place from April 8 to July 18, 2014, focusing on beef cattle production. Activities included nutritional, reproductive, and health management, genetic improvement, pregnancy diagnosis, disease control, and technical and administrative support. Special emphasis was placed on participation in the Natura® genetic improvement program, with evaluation of animal performance and breeding traits. The internship offered valuable practical experience and helped consolidate theoretical knowledge gained during the undergraduate program.
Supervised internship report in veterinary medicine: in the area of beef cattle farming
Keywords: Beef cattle; Genetic improvement; Manejo reprodutivo; Estágio supervisionado; Bovinocultura de corte; Melhoramento genético; Reproductive management; Supervised internship; CNPQ::CIENCIAS AGRARIAS